2023
DOI: 10.1128/spectrum.03288-22
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis Outer Membrane Vesicles Promote Apoptosis via msRNA-Regulated DNA Methylation in Periodontitis

Abstract: P. gingivalis is a bacterium often associated with periodontitis. This study demonstrates that (i) sRNA45033 in P. gingivalis OMVs targets CBX5, (ii) CBX5 regulates the methylation of p53 DNA and its expression, which is associated with apoptosis, and (iii) a novel mechanism of interaction between hosts and pathogens is mediated by OMVs in the occurrence of periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“… 35 The purified MVs from S. aurues USA300 were 55.23 ± 8.17 nm in diameter, consistent with previous studies. 23 , 36 We confirmed that 5 μg of USA300-derived MVs is safe for C57BL/6 mice. However, the survival rates of the MV-challenged mice decreased with increasing MV dose, and 20 μg of USA300 MVs killed all tested mice within 24 h post-injection ( Figure 1D ).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“… 35 The purified MVs from S. aurues USA300 were 55.23 ± 8.17 nm in diameter, consistent with previous studies. 23 , 36 We confirmed that 5 μg of USA300-derived MVs is safe for C57BL/6 mice. However, the survival rates of the MV-challenged mice decreased with increasing MV dose, and 20 μg of USA300 MVs killed all tested mice within 24 h post-injection ( Figure 1D ).…”
Section: Discussionsupporting
confidence: 67%
“… 14 S. aureus MVs can package an array of prototypic pore-forming toxins, including alpha-hemolysin, delta-hemolysin, and leukocidins. 28 , 36 However, the selective cytotoxicity of S. aureus MVs against tumor cells is unclear. One possible explanation is that the expression levels of toxin receptors vary between tumorous and non-carcinomatous cells; however, this explanation requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Growing lines of studies have demonstrated that bacterial EVs are one of the vital underlying mechanisms behind the pathogenesis of various diseases (Xie et al 2023). It has proven that outer membrane vesicles derived from periodontal pathogens such as Porphyromonas gingivalis (Fan et al 2023) and Fusobacterium nucleatum (Chen et al 2022) could promote the progression of experimental periodontitis in mice. However, whether and how E. faecalis , as a resistant bacterium in persistent endodontic infection, could contribute to apical periodontitis pathogenesis through EVs has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Further, small RNAs could be delivered to the host cellular immune system via OMVs of P. gingivalis , A. actinomycetemcomitans , and T. forsythia [ 146 ]. For example, Pg -EVs can target chromobox 5 (CBX5) of PDLCs through sRNA45033 in OMVs, and promote apoptosis by regulating the methylation of p53 [ 147 ]. OMVs of periodontal pathogenic bacteria can also interact with host immune cells.…”
Section: Bevs and Periodontal Regenerationmentioning
confidence: 99%